Security and Interoperable Medical Device Systems, Part 2: Failures, Consequences and Classifications - Vasserman, Eugene Y.; Venkatasubramanian, Krishna K.; Sokolsky, Oleg; Lee, Insup (IEEE Computer Society; Institute of Electrical and Electronics Engineers, 2013)
Interoperable medical devices (IMDs) face threats due to the increased attack surface presented by interoperability and the corresponding infrastructure. Introducing networking and coordination functionalities fundamentally alters medical systems' security properties. Understanding the threats is an important first step in eventually designing security solutions for such systems. Part 2 of this two-part article defines a failure model, or the specific ways in which IMD environments might fail when attacked. An attack-consequences model expresses the combination of failures experienced by IMD environments for each attack vector. This analysis leads to interesting conclusions about regulatory classes of medical devices in IMD environments subject to attacks. Part 1 can be found here: http://doi.ieeecomputersociety.org/10.1109/MSP.2012.128.
Keywords: Integrated Clinical Environment (ICE); Attack model, attack vectors; Computer security; Interoperable medical devices; Interoperability; Medical devices